2019
DOI: 10.4018/ijcwt.2019100103
|View full text |Cite
|
Sign up to set email alerts
|

Cyber Counterintelligence

Abstract: This article advances a conceptual framework for cyber counterintelligence (FCCI) as a theoretical construct, hopefully useful not only to this field's academic development, but also to sound practice. It is submitted within the context of the sharp increasing targeting of state and non-state actors by adversarial intelligence actors (such other nation states, crime syndicates and competitors). The signature role of cyber counterintelligence (CCI) is precisely the engagement, exploitation and neutralisation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…It is no longer refutable that traditional cybersecurity measures are not enough. Therefore, this confirms an emergent and critical need for organisations to adopt and invest, predominantly, in Thenjiwe Sithole, Jaco Du Toit and Sebastian H von Solms cyber counterintelligence (CCI), which is a multi-disciplinary and proactive measure that can identify, deter, prevent, destruct, exploit and neutralise adversarial attempts to collect, alter or breach the CIA of critical information systems through cyber means (Duvenage & von Solms, 2015).…”
Section: Introductionmentioning
confidence: 55%
See 1 more Smart Citation
“…It is no longer refutable that traditional cybersecurity measures are not enough. Therefore, this confirms an emergent and critical need for organisations to adopt and invest, predominantly, in Thenjiwe Sithole, Jaco Du Toit and Sebastian H von Solms cyber counterintelligence (CCI), which is a multi-disciplinary and proactive measure that can identify, deter, prevent, destruct, exploit and neutralise adversarial attempts to collect, alter or breach the CIA of critical information systems through cyber means (Duvenage & von Solms, 2015).…”
Section: Introductionmentioning
confidence: 55%
“…In their previous research, the authors identified and defined the first two elements of the CCI Competence Framework, namely CCI Dimensions and CCI Functional Areas (see Figure 1). As Figure 1 also shows, the construct of these two elements aligns with the concept of the four dimensions of counterintelligence (Prunckun, 2019) and the CCI (Duvenage & von Solms, 2014). The paragraph above demonstrated that two Elements of the CCI Competence Framework (Figure 1) had been developed in preceding research.…”
Section: Identifying Job Roles For the CCI Competence Frameworkmentioning
confidence: 65%
“…In fact, "mature offensive cyber capability" includes "intelligence collection and analysis" (Devanny, Goldoni and Medeiros, 2022), as well as cyber counterintelligence (CCI). The latter in turn includes substantial defensive facets (Duvenage, 2019). Cavelty (2018) rightly points out that the Global North's discourse was until very recently all about the offensive domination of one actor over others-be it through hard and/or soft power.…”
Section: 'Offensive' Dimensionmentioning
confidence: 99%
“…As illustrated in Figure 1 below, by dotted lines on the active-defensive quadrant, the ACD falls on the activedefensive quadrant of the cyber counterintelligence (CCI) model (Ntingi, Duvenage, du Toit & von Solms, 2022). Even though the tools and techniques used to conduct activities of active cyber offence and active cyber defence are the same, active cyber defence aims to strengthen the cyber defences of an organisation rather than intrusive actions towards the adversaries (Duvenage, Jaquire & von Solms., 2020a;Ntingi, et al, 2022). Our focus is on the cybersecurity operations of organisations, particularly SMMEs, to strengthen their cyber defences and actively defend their ICT systems without resorting to intrusive actions against adversaries.…”
Section: Conceptualisation Of 'Active Cyber Defence'mentioning
confidence: 99%
“…According to Burke (2020), the United Kingdom (UK) and the United States of America (USA) are among the countries that incorporate defensive AI technologies into their cybersecurity strategies. Duvenage, Jaquire & von Solms (2020b) state that the convergence of emerging technologies such as AI, the Internet of Things, Big Data, and social media is important in strengthening efforts to cybersecurity defences. Furthermore, Duvenage, et al, (2020b) also alludes that these technologies are not only useful for large organisations and nation-states but also for smaller organisations with limited resources.…”
Section: Optimisation Of Acd Using Artificial Intelligence (Ai)mentioning
confidence: 99%